Synergistic effect of ultrasound and light to efficient singlet oxygen formation for photodynamic purposes. (February 2023) - Granados-Tavera, Kevin; Zambrano-Angulo, Michael; Montenegro-Pohlhammer, Nicolas; Yaşa Atmaca, Göknur; Sobotta, Lukasz; Güzel, Emre; Cárdenas-Jirón, Gloria; Erdoğmuş, Ali; Gürek, Ayşe Gül
Abstract: As cancer is one of the leading causes of death globally, it is highly desirable to explore the therapeutic potential of new sensitizers in photodynamic therapy (PDT). In recent years, PDT applications performed with the help of ultrasound have attracted attention. Also, the importance of phthalocyanines, which are used as sensitizers in photodynamic and/or sonodynamic therapy (SDT), is increasing. The most important properties of phthalocyanines for therapeutic applications are their ability to generate reactive oxygen species (ROS) at the appropriate wavelength. To improve ROS production by phthalocyanines applying ultrasounds seems to be the reasonable pathway of development for this treatment method. In this context, to evaluate potentials for sonophotodynamic therapy (SPDT), the syntheses of highly soluble non-peripherally substituted metal-free (2 ), gallium (3 ), and indium (4 ) phthalocyanines were completed by substituting 3-methoxybenzyloxy groups. All prepared compounds were elucidated using many different spectroscopic approaches encompassing Fourier transform infrared (FT-IR), ultraviolet–visible (UV–Vis), 1 H NMR, and matrix-assisted laser deionization/ionization time-of-flight mass spectroscopy (MALDI-TOF MS) techniques. Additionally, photophysical, photochemical, and sono-photochemical evaluations of the novel phthalocyanines are presented. The combination of ultrasound and light had an enhancing effect on singlet oxygen production in all phthalocyanine derivatives (2 –4 ). Singlet oxygen quantum yields increased between 50% and 80% for metal-free, gallium, and indium phthalocyanines. Density Functional Theory (DFT) and time-dependent (TD-DFT) were used for the description of optical and electronic properties of metal-free, gallium, and indium phthalocyanines. The Spin Orbital Coupling Constant (SOCC) for these molecules was also calculated through the quasi-degenerate perturbation theory method. Considering the singlet and triplet states of lower energy, we have calculated the most probable intersystem spin crossing (ISC) pathways. Our results suggest that all the phthalocyanines have potential application in PDT, however, indium phthalocyanine has greater applicability in PDT. Graphical abstract: Image 1 Highlights: Syntheses of highly soluble phthalocyanines were completed by substituting 3-methoxybenzyloxy groups. Photophysical, photochemical, and sono-photochemical properties of the novel phthalocyanines are presented. Combination of ultrasound and light had an enhancing effect on singlet oxygen production in all phthalocyanine derivatives. The Spin Orbital Coupling Constant (SOCC) and most probable intersystem spin crossing (ISC) pathways are calculated. 3-methoxybenzyloxy substituted indium phthalocyanine has great applicability in photodynamic purposes.